Improving transgenic approaches to mosquito population control - Conway, M (2014)
The disease vectors Aedes aegypti and Aedes albopictus are serious and growing threats to global health. As vectors of the arboviruses dengue fever and chikungunya, these mosquitoes are responsible for hundreds of millions of cases and thousands of deaths each year. Absent specific treatments or vaccines, effective control of mosquito populations remains the only option for tackling a growing public health challenge. More effective control tools are urgently needed. Recently, a novel approach to pest population control has been developed based on the release of insects carrying a repressible, dominant lethal allele. This approach has achieved dramatic reductions in Ae. aegypti populations in regulated open field experiments. Despite this success, there remains scope to improve upon the current technology. It is proposed that an 'ideal' strain would combine the following features: (i) repressible lethality in late juvenile phases; (ii) a mechanism for removing females at an early developmental stage in the release generation; and (iii) orthogonal expression control mechanisms allowing both these systems to be combined in a single strain. This thesis describes research undertaken in pursuit of a 'next generation' strain. Two novel promoters from putative Osiris genes have been identified which confer a 102-103 – fold up-regulation in transgene expression specific to late pupal stages. One of these 'Osiris' promoters has been used to develop transgenic Aedes aegypti strains. 5 lines showed pupal-specific lethality of 98-100% penetrance, which was repressed in the presence of tetracycline. An Ae. albopictus orthologue of the sex-determining gene doublesex (dsx) has been isolated and characterised and a female-specific expression system developed. Transgenic lines show female-specific expression of a transgene; however, there remains some 'leaky' expression in male insects. Finally, a potential expression control tool based on an auxin-inducible expression system has been investigated. 11 different transgenic lines were developed based on three different construct designs. None showed auxin-inducible expression of a transgene.